2018
DOI: 10.1016/j.radcr.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

A case with iatrogenic pneumothorax due to deep dry needling

Abstract: Deep dry needling is an evidence-based treatment technique that is accepted and used by physical therapists for treatment of musculoskeletal pain. We present a case of iatrogenic pneumothorax due to deep dry needling over the posterior thorax. A 36-year old presented with right chest pain 2 hours after dry needling for pain in his back muscles. Chest radiograph suggested small right pneumothorax and the finding was confirmed by computed tomography. Not only should practitioners and their patients be aware of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…However, major adverse events, e.g., pneumothorax, have been also reported in some cases, although their rate is less than 0.1% (1 per 1024 needling treatments) and depend on the anatomical location. In fact, case reports describing pneumothorax after dry needling have applied the intervention over the thoracic, and not cervical spine, muscles [ 61 , 62 ]. Although dry needling could be considered a safe treatment if properly applied, potential risks associated with its application on each body area where it is applied should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…However, major adverse events, e.g., pneumothorax, have been also reported in some cases, although their rate is less than 0.1% (1 per 1024 needling treatments) and depend on the anatomical location. In fact, case reports describing pneumothorax after dry needling have applied the intervention over the thoracic, and not cervical spine, muscles [ 61 , 62 ]. Although dry needling could be considered a safe treatment if properly applied, potential risks associated with its application on each body area where it is applied should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers did not observe a difference in mitochondrial function between any of the three biopsied muscles and they concluded that abnormal mitochondria function does not seem to play a role in the development of TrPs. Yet, studies by Reitinger and Windish showed the presence of ragged red fibers near TrPs (Reitinger et al, 1996;Windisch et al, 1999), which are indicative of an impaired oxidative metabolism. While these studies have been criticized as the tissue samples were taken from cadavers, others found differences in mitochondrial and lipid droplet morphology in female office workers with trapezius myalgia with a significantly higher percentage of intermyofibrillar lipid droplets touching the mitochondria in the patient group compared to the control group (De Meulemeester et al, 2019).…”
Section: Basic Researchmentioning
confidence: 99%
“…Although serious adverse events following DN are relatively rare (Brady et al, 2014), clinicians must always be aware that DN should only be utilized against the background of outstanding knowledge of three-dimensional anatomy. Severe complications include pneumothorax (Cummings et al, 2014;Uzar et al, 2018), infection (Kim et al, 2018), and epidural hematoma (Lee et al, 2011). In this case report from Washington DC, USA, the authors describe a 62-year old female who as part of her physiotherapy program was treated with DN of TrPs in the right infraspinatus, rhomboids, trapezius, and bilateral C3eC4 and C4eC5 multifidus muscles.…”
Section: Dry Needling Acupuncture and Injectionsmentioning
confidence: 99%
“…While most commonly DN is directed at trigger points [2], its contemporary use also targets tendons [3,4], entheses [5], periosteum [6], scar tissue [7], and fascia [8] to reduce local and referred pain, lessen spasticity [9,10], eliminate neural entrapments [11], increase range of motion [12], or normalize muscle activation patterns [13]. DN is a safe anatomy-driven procedure [14], although there are inherent risks when safety precautions are not taken into account [15][16][17][18]. From 2013 to 2017, the database of CNA (the underwriting company for the APTA-endorsed physical therapy professional liability insurance plan) showed a total of 34 claims in 19 different states arising from DN practice.…”
Section: Editorialmentioning
confidence: 99%